2000
DOI: 10.1046/j.1464-5491.2000.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of C‐peptide on incipient nephropathy and neuropathy in patients with Type 1 diabetes mellitus

Abstract: These results indicate that combined treatment with C-peptide and insulin for 3 months may improve renal function by diminishing urinary albumin excretion and ameliorate autonomic and sensory nerve dysfunction in patients with Type 1 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
201
0
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(214 citation statements)
references
References 29 publications
8
201
0
5
Order By: Relevance
“…However, over the last decade, several reports have suggested that C-peptide may exert a number of physiological effects, which are probably mediated by stimulation of Na + ,K + -ATPase and endothelial nitric oxide synthetase activities in several tissues [23]. In the early stage of type 1 diabetes, C-peptide replacement results in diminished UAE rate and ameliorates nerve dysfunction [24]. Based on these findings, lack of Cpeptide itself might be one of the causal factors in the development of microangiopathy in fulminant type 1 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, over the last decade, several reports have suggested that C-peptide may exert a number of physiological effects, which are probably mediated by stimulation of Na + ,K + -ATPase and endothelial nitric oxide synthetase activities in several tissues [23]. In the early stage of type 1 diabetes, C-peptide replacement results in diminished UAE rate and ameliorates nerve dysfunction [24]. Based on these findings, lack of Cpeptide itself might be one of the causal factors in the development of microangiopathy in fulminant type 1 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, C-peptide has been shown to exert insulin-independent biological effects on a variety of cells, where it affects the activation of several intracellular pathways, such as, but not limited to, those involved in cellular proliferation and inflammation [2][3][4]. Importantly, C-peptide has been demonstrated to be beneficial when administered as replacement therapy to type 1 diabetes patients who suffer from some diabetic complications [5][6][7][8]. How exactly C-peptide achieves its intracellular effects in target cells, however, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of these enzyme systems is of particular interest in diabetes, since both are reported to be deficient in this disorder [9][10][11][12]. Studies in animal models of diabetes and in patients with type 1 diabetes demonstrate that administration of Cpeptide, to yield physiological concentrations, results in a substantial improvement of diabetes-induced functional and structural changes in peripheral nerves [13][14][15]. In addition, there is evidence to indicate that C-peptide prevents diabetes-induced deficits in nerve fibre regeneration [16], protects against glucose-induced apoptosis of nerve cells and stimulates cellular proliferation [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is evidence to indicate that C-peptide prevents diabetes-induced deficits in nerve fibre regeneration [16], protects against glucose-induced apoptosis of nerve cells and stimulates cellular proliferation [17,18]. Moreover, C-peptide in replacement doses corrects the characteristic glomerular hyperfiltration seen in the early stages of diabetic nephropathy, reduces urinary excretion of albumin and prevents the development of glomerular hypertrophy in type 1 diabetes [13,19,20]. In addition, recent studies have established that C-peptide given in replacement doses to type 1 patients augments skeletal muscle and myocardial blood flow and increases the rate of contraction and the stroke volume of the left ventricle [21][22][23].…”
Section: Introductionmentioning
confidence: 99%